Evaluasi Kinerja Perbankan ASEAN Terkait Peningkatan Risiko Sistemik dalam Integrasi Pasar Perdagangan Bebas Masyarakat Ekonomi ASEAN (MEA) - Rinda Siaga Pangestuti (Ekonomis: Journal of Economics and Business, 2020)
This study is aimed to provide an evaluation of banking performance in ASEAN given the inclusion of the ASEAN Economic Community (AEC) which is associated with an increase in potential systemic risk. Some of the main findings in this study are: (a) the increase in systemic risk is influenced by the increase in risk on asset quality as seen from the increase in the percentage of non-performing loans; (b) bank liquidity has a significant positive effect on increasing systemic risk; (c) banks with large capital can exert influence over increased systemic risk (in a 90% confidence level but here we use 95% confidence level). The government is expected to be able to mitigate the increase in potential systemic risks, especially after the integration of free trade in ASEAN.